2011
DOI: 10.1177/1368430210395637
|View full text |Cite
|
Sign up to set email alerts
|

Can moral convictions motivate the advantaged to challenge social inequality?

Abstract: This article examines whether and how moral convictions, defined as strong and absolute stances on moralized issues, motivate advantaged group members to challenge social inequality. Specifically, we propose that violations of moral convictions against social inequality motivate collective action against it by increasing identification with the victims of social inequality. Such identification links the current work with the Social Identity Model of Collective Action (SIMCA; Van Zomeren, Postmes, & Spears,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
339
4
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(376 citation statements)
references
References 42 publications
(108 reference statements)
30
339
4
3
Order By: Relevance
“…As emancipation movements are defined by shared goals rather than mere category membership, they can leave room for allies from advantaged outgroups and thus offer a shared identity. Identifying with the disadvantaged is, in turn, associated with collective action intentions (van Zomeren, Postmes, Spears, & Bettache, 2011).…”
mentioning
confidence: 99%
“…As emancipation movements are defined by shared goals rather than mere category membership, they can leave room for allies from advantaged outgroups and thus offer a shared identity. Identifying with the disadvantaged is, in turn, associated with collective action intentions (van Zomeren, Postmes, Spears, & Bettache, 2011).…”
mentioning
confidence: 99%
“…The psychological pathway by which third parties and outsiders come to appraise a conflict and take collective action is also relatively unexplored (but see Saeri et al, 2015). New research suggest that stable, personal beliefs including moral convictions, Social Dominance Orientation, and Right-wing Authoritarianism can shape appraisals of intergroup conflict and subsequent collective action (Saeri et al, 2015;van Zomeren, Postmes, & Spears, 2012;van Zomeren, Postmes, Spears, & Bettache, 2011). In this work, we investigate how personal values might shape an outsider's appraisals of an external group conflict and lead to collective action.…”
Section: Personal Values About Change and Status Quo Influence Outsidmentioning
confidence: 99%
“…However, recent work has begun to investigate how more stable, personal beliefs may shape these more proximal appraisals. Van Zomeren and colleagues (van Zomeren, Postmes, & Spears, 2012;van Zomeren, Postmes, Spears, & Bettache, 2011) have shown that personal moral convictions about group conflict (e.g., believing that mainland Chinese deserve greater political freedom) can indirectly predict collective action intentions by fostering identification with the affected group. Saeri et al (2015) have shown that personal political ideologies of Social Dominance Orientation (Pratto, Sidanius, Stallworth, & Malle, 1994) and Right-wing Authoritarianism (Altemeyer, 1981) can shape proximal appraisals both sympathetic to a disadvantaged group (e.g., Russian protestors against government corruption) and sympathetic to an advantaged group (e.g., the Russian government with a goal of quelling protests).…”
Section: Extending the Pathways To Actionmentioning
confidence: 99%
“…The psychological pathway by which third parties and outsiders come to appraise a conflict and take collective action is also relatively unexplored (but see Saeri et al, in press). New research suggest that stable, personal beliefs including moral convictions, Social Dominance Orientation, and Right-wing Authoritarianism can shape appraisals of intergroup conflict and subsequent collective action (Saeri et al, in press;van Zomeren, Postmes, & Spears, 2012;van Zomeren, Postmes, Spears, & Bettache, 2011). In this work, we investigate how personal values might shape an outsider's appraisals of an external group conflict and lead to collective action.…”
Section: Personal Values About Change and Status Quo Underpin Outsidementioning
confidence: 96%
“…Members of high-status group may act to defend their status against an agitating low-status group (Ellemers, Doosje, Van Knippenberg, & Wilke, 1992;Iyer, Leach, & Crosby, 2003;Leach, Snider, & Iyer, 2002), rather than merely failing to support the low-status group. Moral convictions, as stable and inviolable attitudes about a specific intergroup conflict, have been found to predict collective action intentions (van Zomeren, Postmes, & Spears, 2012;van Zomeren, Postmes, Spears, & Bettache, 2011). But each of these embedded assumptions is challenged by outsider collective action.…”
Section: Collective Action Beyond the Conflict Contextmentioning
confidence: 99%